Toward an Urban Sector Strategy : Georgia's Evolving Urban System and its Challenges - World Bank (Washington, DC, 2014)
This review analyzes the profile, trends and challenges of Georgia's changing urban landscape since independence in 1991 and provides policy suggestions to facilitate the economic transition of the country through its cities. In its analysis and subsequent recommendations on policy interventions, this report draws on a program of diagnostics called the 'Urbanization Review' (UR). The UR diagnostic is based on three main pillars of urban development which have emerged as key areas of policy engagement for successful cities. These are: a) planning, charting a course for cities by setting the terms of urbanization, especially policies for using urban land and expanding basic infrastructure and public services; b) connecting, physically linking people to jobs, and businesses to markets; and c) financing, raising and leveraging up-front capital to meet the increasing demand for infrastructure and services. In moving forward, the review recommends that Georgia focus on: a) developing a national urban strategy that recognizes the contribution of each city to the overall economy, i.e. a 'systems of cities' approach that can assist in reducing regional disparities; b) assisting cities to develop urban plans, including local economic development plans, c) reforming building and planning codes; and d) assisting cities in improving their local governance and finances.